Penerapan Permainan Edukatif ‘Seblak Prasmanan’ dalam Pembelajaran Perkalian pada Siswa Kelas 3 Sekolah Dasar - Syifa Nur Haliza; Syafirda Azmi Auliya; Diah Putri Rahmawati; Dian Mustika Anggraini (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Mathematics learning at the elementary school level plays an important role in shaping students' logical thinking. However, understanding multiplication concepts remains a challenge for some students, mainly due to the learning process which tends to be monotonous and lacks active participation. This study aims to describe the implementation of context-based educational games "Seblak Prasmanan" and to examine their impact on students' activity and understanding in multiplication material. The study uses a descriptive qualitative approach with 21 third-grade students at MI Miftahul Ulum 02 Honggosoco as subjects. Data collection techniques were conducted through direct observation and documentation with the help of observation sheets containing indicators of student involvement and understanding. The results of the study show that the implementation of educational games can encourage students to participate more actively in learning. In addition, students find it easier to understand the concept of multiplication as repeated addition through contextual learning experiences. A more enjoyable learning atmosphere also impacts the increase in students' interest and motivation to learn. Thus, the use of educational games based on everyday life contexts can be an alternative learning strategy to effectively improve the quality of mathematics learning in elementary schools.